Self-disgust and Self-forgiveness: The Mediating Roles of Trait and State Guilt, Internal and External Shame, Empathic Concern, and Personal Distress - Taysí, Ebru; Orçan, Fatíh (Psychology Hub, 2025)
Self-disgust and self-forgiveness would superficially appear to correlate negatively, but their empirical relationship has not yet been closely analyzed. Here, two studies of undergraduate students are reported that explore this relationship through a new model combining the emotional determinants of self-forgiveness and a biopsychosocial approach to shame. Study 1 (N = 290) investigates whether this relationship is mediated by internal and external shame, empathic concern, or personal distress. In Study 2 (N = 278), trait and state guilt are added to the first model of self-forgiveness. Structural equation modeling reveals that self-disgust and self-forgiveness are related to one another, but their association is mediated by external and internal shame and personal distress. Internal shame is also found to mediate the relationship between self-disgust and self-forgiveness alone, while trait and state guilt do not mediate this relationship. A new model is presented with these new findings, and implications are discussed.